Comments and improvements of “HOTA: Handover optimized ticketbased authentication in networkbased mobility management” - Alizadeh, Mojtaba; Tadayon, Mohammad Hesam; Sakurai, Kouichi; Baharun, Sabariah; Anada, Hiroaki; Zamani, Mazdak; Akram, M. Zeki; Chaudhry, Shehzad Ashraf; Khan, Muhammad Khurram (IEEE, 2017)
Nowadays, various mobile devices are being an inseparable part of our normal life. Mobile users tend to be connected to the Internet seamlessly, which is provided by mobility management protocols. One of the latest mobility management protocol is Proxy Mobile IPv6 (PMIPv6), which is a networkbased protocol. Authentication mechanism as a critical security procedure is not specified in PMIPv6, hence various authentication methods have been proposed. Lee and Bonin proposed a ticketbased authentication scheme for PMIPv6, which is called HOTA in 2013. Even though, HOTA offers some security protection mechanisms, but is vulnerable to DoS attack. Furthermore, we show other existing drawbacks to the scheme such as vulnerability against desynchronization attack and Session Hijacking attack. In this paper, we propose an enhancement method to mitigate these security drawbacks. Finally, security and performance of the proposed method are analyzed and compared to HOTA method